2016
DOI: 10.1371/journal.pone.0165609
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Tissue Factor Pathway Inhibitor 2, a Serum Biomarker Candidate for Ovarian Clear Cell Carcinoma

Abstract: BackgroundThere is currently no reliable serum biomarker for ovarian clear cell carcinoma (CCC), a highly lethal histological subtype of epithelial ovarian cancer (EOC). Previously, using a proteome-based approach, we identified tissue factor pathway inhibitor 2 (TFPI2) as a candidate serum biomarker for CCC. In this study, we sought to evaluate the clinical diagnostic performance of TFPI2 in preoperative prediction of CCC.MethodsSerum TFPI2 levels were measured in serum samples from a retrospective training s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 39 publications
4
51
0
Order By: Relevance
“…TFPI2 is an inhibitor of the tissue factor pathway involved in blood coagulation. Gene expression of TFPI2 was decreased in samples of bladder tumors (43) and cervical tumors (44), while TFPI2 protein concentrations in serum were higher in ovarian clear cell adenocarcinoma patients (45,46). Hypermethylation, generally associated with decreased gene expression (47), was detected for TFPI2 in multiple types of cancer compared to normal adjacent tissues (48)(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TFPI2 is an inhibitor of the tissue factor pathway involved in blood coagulation. Gene expression of TFPI2 was decreased in samples of bladder tumors (43) and cervical tumors (44), while TFPI2 protein concentrations in serum were higher in ovarian clear cell adenocarcinoma patients (45,46). Hypermethylation, generally associated with decreased gene expression (47), was detected for TFPI2 in multiple types of cancer compared to normal adjacent tissues (48)(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…The blood samples were prepared for inductively coupled plasma-mass spectrometry (ICP-MS; operating conditions in Supplementary Table 1) by a direct alkali dilution method (30). Briefly, blood samples were diluted 1:17-44 with an alkali solution consisting of 2% butanol (Honeywell Research Chemicals, Germany), 0.05% EDTA (Sigma-Aldrich, USA), 0.05% Triton X-100 (Sigma-Aldrich), 1% NH 4 OH (Romil, UK), and 20 µg/g internal standards 45 Sc, 72 Ge, 103 Rh, 175 Lu, and 193 Ir. Before analysis, the diluted samples were sonicated for 5 min, and centrifuged at 694 g for 5 min.…”
Section: Arsenic Exposure and Metabolism Efficiency Assessmentmentioning
confidence: 99%
“…Published in 2019, Kobayashi et al made a literature review about the advances in the imaging and the non-invasive tests and biomarkers of early detection of the malignant transformation of benign ovarian endometrioma to endometriosis-associated ovarian cancer (23). Several techniques are investigated such as electronic absorption spectroscopy of cyst fluid hemoglobin or dosage of serum Tissue Factor Pathway Inhibitor-2 (TFPI2) (elevated with malignant transformation) (24).…”
Section: Discussionmentioning
confidence: 99%
“…Currently available serum-based tests, including CA125, have been disappointing (4). Arakawa et al (21), reported that serum Tissue Factor Pathway Inhibitor-2 (TFPI2) levels were elevated only in patients with CCC among epithelial ovarian cancer. The preliminary study demonstrated that patients with endometriosis presented mild-to-moderate elevation of serum CA125 levels, but may be characterized by normal serum levels of TFPI2 (21).…”
Section: Discussionmentioning
confidence: 99%